The influence of menu diversity, price perception, social media on repurchase interest through customer satisfaction of msmes in gado-gado, ketoprak, karedok traditional foods in south Tangerang, Indonesia - Rahayu Lestari; Rosle Mohidin; Suddin Lada (Penerbit Universiti Malaysia Sabah, 2025)
This study examines the influence of menu diversity, price perception, and social media on repurchase interest, mediated by customer satisfaction, among traditional food MSMEs specializing in Gado-Gado, Ketoprak, and Karedok in South Tangerang. Primary data were collected through questionnaires distributed to 85 respondents, selected using purposive sampling based on their frequency of purchasing from these MSMEs. The data were analyzed using Partial Least Squares (PLS) with the Smart PLS 3.0 application. The results indicated that, partially, menu diversity and customer satisfaction significantly affect repurchase interest. Social media positively and significantly influences both customer satisfaction and repurchase interest. However, price perception insignificantly impacts customer satisfaction, though it does affect repurchase interest. Interestingly, while menu diversity enhances customer satisfaction, it does not directly influence repurchase interest. These findings highlight the complex interplay of factors driving repurchase behavior and provide valuable insights for MSMEs aiming to enhance customer retention and satisfaction through strategic menu offerings, social media engagement, and competitive pricing